Literature Review of Integrated Water Resources Management (IWRM) in Transboundary River Basins - Yayan Oktiawan; Alex Irawan Trianto; Ollga Febiola; Arya Ningsih; Destra Amni; Santi Mareta; Losita Dewi; Delfi Kurnia Zebua (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
This study aims to determine the management of integrated water resources (IWRM) in cross-border river areas. This type of research is a literature review research. The data sources in the study analyzed several relevant literatures. The keywords for searching for data sources are water resources, off-limits rivers; and river flow. Data analysis techniques in the study are through qualitative analysis using atlas.id application. The results of this study conclude and best practices in the application of IWRM in various geographical and institutional contexts. The results of the review show that IWRM is a crucial approach in overcoming the problem of transboundary water management, but still faces various obstacles such as lack of coordination between countries, conflicts of interest, and climate change. This research highlights the importance of international cooperation, community participation,